SEPENGGAL FENOMENA SEPUTAR WACANAISTILAH SENI KRIYA DAN PERKEMBANGANNYA D E WAS A INI Sekilas Perkembangan Kriya Tekstil di ISI Yogyakarta - Suryo Tri Widodo (Ars: Jurnal Seni Rupa dan Desain, 2007)
Discourses and developments o f art craft itr Indonesia arc always interesting to be discussed.Discourses on the term of "seni kriya" are, in fact, inseparable from the similar one, i.e. "kriya ". The term"seni kriya" and "kriya", indeed, possess different cultural background. When an artist creates a worko f art craft, he/she does not concern about these discourses. On the contrary, in an academic level, thesediscourses can sometimes become a problem, especially when it comes to giving the meaning of art craft.This article attempts to discuss those problems. At first, there will be a description about the origino f the term “seni kriya", in addition to the explanation on the term "kriya ". Liter, the present conditiono f art craft discourses will be presented. The last presentation would be the development oj art-crafi works.In order to provide the reader with more clear explanation, the development happened in the Department ofCraft, the Faculty o f Visual A rt, ISI Yogyakarta-especially in the textile art craft made by the department’sstudents - are included.Keywords: art discourse, craft (high art), craft textiles